A Loyal Base: Support for Authoritarian Regimes in Times of Crisis - Anja Neundorf; Aykut Ozturk; Ksenia Northmore-Ball; Katerina Tertytchnaya; Johannes Gerschewski (Comparative Political Studies, 2024)
Does citizen belief in the non-instrumental principles of the political regime, such as strongman leadership, patriotism, or attachment to a charismatic leader, collectively known as normative support, help stabilize authoritarian regimes? While a large literature recognizes that authoritarian regimes depend on popular support to lower the costs of staying in power, existing research mainly views mass support for these regimes as instrumental, fuelled by performance. Using novel experimental evidence from two original online surveys fielded in Turkey and observational data, we find high levels of normative support for Turkey's authoritarian rule. Further, our results demonstrate that instrumental and normative dimensions of support may be more closely related than previously theorized. Importantly, we show that both forms of support prevent voter defections in times of crisis. These findings, which revisit the importance of citizens' support for regime resilience, have implications for research on mass opinion and defection cascades in electoral autocracies.
Keywords: 320; authoritarian regimes; public opinion; economic crises; survey experiments; Turkey